2007
DOI: 10.1177/1533317507305178
|View full text |Cite
|
Sign up to set email alerts
|

How Do Officially Organized Services Meet the Needs of Elderly Caregivers and Their Spouses With Alzheimer's Disease?

Abstract: The caregiving situation among caregivers and their spouses with Alzheimer's disease, the support and services received, the unmet needs, and the caregivers' satisfaction with the services are examined. The study included a survey of a random sample of 1943 caregivers of persons with Alzheimer's disease in Finland. Mean age of the caregivers was 78.2 years, and 35% had poor subjective health. Disabilities and behavioral symptoms were common among the spouses with Alzheimer's disease. The services most often of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 31 publications
3
63
0
3
Order By: Relevance
“…Hence individual support/services may not have an effect on the overall situation of the caregivers. A recent study from Finland (Raivio et al, 2007) showed that official services are inadequate in meeting the needs of caregivers of persons with dementia, and that there must be more collaboration and consideration of the needs and wishes of the caregivers before services are provided.…”
Section: Discussionmentioning
confidence: 99%
“…Hence individual support/services may not have an effect on the overall situation of the caregivers. A recent study from Finland (Raivio et al, 2007) showed that official services are inadequate in meeting the needs of caregivers of persons with dementia, and that there must be more collaboration and consideration of the needs and wishes of the caregivers before services are provided.…”
Section: Discussionmentioning
confidence: 99%
“…Different theories are defined in publications: they do not meet caregivers' expectations or requirements (63), families are convinced that they provide more stress than relief (64-66), they produce a sense of guilt towards patients (64).…”
Section: Balneotherapy: a New Respite Organization For Both Alzheimermentioning
confidence: 99%
“…The lack of respite care is not only a Norwegian phenomenon; it was also a problem in Canada (33), Finland (34) and Sweden (35). Harrison and Neufeld (36) reported some carers had several barriers requesting support for themselves.…”
Section: Lacking Sufficient Orcmentioning
confidence: 99%